HuR contributes to Hepatic Stellate Cell activation and liver fibrosis - Woodhoo, A. (2012)
RNA-binding proteins (RBPs) play a major role in control of mRNA turnover and translation rates. We examined the role of the RBP human antigen R (HuR) during cholestatic liver injury and hepatic stellate cells (HSC) activation. HuR silencing attenuated fibrosis development in vivo after BDL, reducing liver damage, oxidative stress, inflammation, and collagen and α-SMA (α-smooth muscle actin) expression. HuR expression increased in activated HSC from BDL mice and during HSC activation in vitro, and HuR silencing markedly reduced HSC activation. HuR regulated platelet-derived growth factor (PDGF)-induced proliferation and migration, and controlled expression of several mRNAs involved in these processes (Actin, MMP9, Cyclin D1 and B1). These functions of HuR were linked to its abundance and cytoplasmic localisation, controlled by PDGF, via ERK and PI3K activation, and ERK-LKB1 activation respectively. More importantly, we identified the tumor suppressor LKB1 as a novel downstream target of PDGF-induced ERK activation in HSC. HuR also controlled transforming growth factor beta (TGF-β-induced profibrogenic actions by regulating expression of TGF-β, α-SMA, and p21. This was likely due to an increased cytoplasmic localisation of HuR, controlled by TGF-β-induced p38 MAPK activation. Finally, we found that HuR and LKB1 (Ser428) levels were highly expressed in activated HSC in human cirrhotic samples. Conclusion: Our results show that HuR is important for pathogenesis of liver fibrosis development in the cholestatic injury model, for HSC activation, and for the response of activated HSC to PDGF and TGF-β.